2022
DOI: 10.1177/00219096221130350
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Factors Affecting the Adoption of Integrated Farming System in Dryland Areas of Southern India by Using Supervised Learning Techniques

Abstract: Smallholders of dryland ecosystems continue to live below the poverty line while facing significant economic and social deprivation with decreasing landholding. Most dryland farmers perform conventional disintegrated farming practices due to a lack of knowledge and resource inefficiency. This study investigates the possibility of an Integrated Farming System (IFS) to address the current dryland farming issues and explore various factors affecting its adoption among the farming community. This study aims to app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…Furthermore, it was observed that in the overall scenario, total livestock units were higher in adopters as compared to nonadopters, which suggested the role of livestock in system integration due to the importance of manure recycling within the farm. Similar observations were reported by Akshitha and Dolli (23). Adoption of integrated farming systems fetched higher income as compared to that of non-adopters due to synergism among different components while reducing the cost of cultivation through resource recycling within the system, which is the basic principle of IFS.…”
Section: Discussion Socio-economic Profile Of Respondentssupporting
confidence: 83%
See 2 more Smart Citations
“…Furthermore, it was observed that in the overall scenario, total livestock units were higher in adopters as compared to nonadopters, which suggested the role of livestock in system integration due to the importance of manure recycling within the farm. Similar observations were reported by Akshitha and Dolli (23). Adoption of integrated farming systems fetched higher income as compared to that of non-adopters due to synergism among different components while reducing the cost of cultivation through resource recycling within the system, which is the basic principle of IFS.…”
Section: Discussion Socio-economic Profile Of Respondentssupporting
confidence: 83%
“…The study finds that age and education influence the adoption of IFS positively. The age of respondents as a proxy for experience had a significant positive influence on IFS adoption (23,24,35). It is believed that influences adoption by boosting a farmer's ability to "perceive, interpret, and respond to new events in the context of risk" (48).…”
Section: Factors Influencing Ifs Adoptionmentioning
confidence: 99%
See 1 more Smart Citation